Synthesis Optimization on Galois-Field Based Arithmetic Operators for Rijndael Cipher - Petrus Mursanto (Journal of ICT Research and Applications, 2011)
A  series  of  experiments  has  been  conducted  to  show  that  FPGA synthesis  of  Galois-Field  (GF)  based  arithmetic  operators  can  be  optimized automatically  to  improve  Rijndael  Cipher  throughput.  Moreover,  it  has  been demonstrated  that  efficiency  improvement  in  GF  operators  does  not  directly correspond to the system performance at application level. The experiments were motivated by so many research works that focused on improving performance of GF  operators.  Each  of  the  variants  has  the  most  efficient  form  in  either  time (fastest) or space  (smallest occupied area) when implemented in FPGA chips. In fact,  GF  operators are not utilized  individually, but  rather integrated one to the others to  implement algorithms.  Contribution  of  this  paper  is  to  raise  issue  on GF-based  application  performance  and  suggest  alternative  aspects  that potentially  affect  it.  Instead  of  focusing  on  GF  operator  efficiency,  system characteristics are worth considered in optimizing application performance.